ANALISA PROFIL KADAR C-REACTIVE PROTEIN PADA STATUS KESEHATAN PERIODONTAL PASIEN DIABETES MELITUS TIPE 2 (Studi di Rumah Sakit Islam Sultan Agung Semarang) - Nirmala Yekti; Yayun Siti Rochmah; Rochman Mujayanto (ODONTO : Dental Journal, 2014)
Background: Periodontitis is the inflammation of periodontal tissue that is characterized by the migration to the apical epithelial jungsional with clinical signs of an increase in probing depth. Periodontitis is one of the oral manifestations in patients with DM. CRP is a protein alpha-globulin produced in the liver and increased levels of inflammatory process in the event. In diabetic patients increased levels of CRP resulted in periodontal tissue destruction. The purpose of this study was to determine the profile of CRP levels in patients with type 2 diabetes mellitus with periodontitis. Method: This research was conducted using analytical observational research methods. The samples used were type 2 diabetes patients with periodontitis and the control group of patients with type 2 diabetes without periodontitis in Sultan Agung Islamic Hospital . All of samples were examined periodontal index, levels of CRP and oral hygiene. Result: Mann Whitney's test show significance p=0.000, which means there are significant differences between groups. Spearman-Kendall's correlation show that relationship between CRP and periodontal index p=0.000 with a correlation coefficient 0.875 means p<0.05 there was that a significant relationship exists between them and the relationship is strong . In relation OH and periodontitis index p=0.030 with a correlation coefficient of 0.650 means p<0.05 there was that a significant relationship exists between them and the relationship strong . Conclusion: It can be concluded that CRP levels in patients type 2 diabetes with periodontitis is higher than the patients type 2 diabetes without periodontitis. And there is a strong relationship between levels of CRP with periodontitis index , and also a strong relationship between periodontitis and OH index .